Increased CSF biomarkers of angiogenesis in Parkinson disease. (24th November 2015) - Janelidze, Shorena; Lindqvist, Daniel; Francardo, Veronica; Hall, Sara; Zetterberg, Henrik; Blennow, Kaj; Adler, Charles H.; Beach, Thomas G.; Serrano, Geidy E.; van Westen, Danielle; Londos, Elisabet; Cenci, M. Angela; et al.
Abstract : Objective: To study biomarkers of angiogenesis in Parkinson disease (PD), and how these are associated with clinical characteristics, blood–brain barrier (BBB) permeability, and cerebrovascular disease. Methods: In this cross-sectional analysis, 38 elderly controls and 100 patients with PD (82 without dementia and 18 with dementia) were included from the prospective Swedish BioFinder study. CSF samples were analyzed for the angiogenesis biomarkers vascular endothelial growth factor (VEGF); its receptors, VEGFR-1 and VEGFR-2; placental growth factor (PlGF); angiopoietin 2 (Ang2); and interleukin-8. BBB permeability, white matter lesions (WMLs), and cerebral microbleeds (CMB) were assessed. CSF angiogenesis biomarkers were also measured in 2 validation cohorts: (1) 64 controls and 87 patients with PD with dementia; and (2) 35 controls and 93 patients with neuropathologically confirmed diagnosis of PD with and without dementia. Results: Patients with PD without dementia displayed higher CSF levels of VEGF, PlGF, and sVEGFR-2, and lower levels of Ang2, compared to controls. Similar alterations in VEGF, PlGF, and Ang2 levels were observed in patients with PD with dementia. Angiogenesis markers were associated with gait difficulties and orthostatic hypotension as well as with more pronounced BBB permeability, WMLs, and CMB. Moreover, higher levels of VEGF and PlGF levels were associated with increased CSF levels of neurofilament light (a marker of neurodegeneration) and monocyte chemotactic protein–1 (a marker of glial activation). The main results were validated in the 2 additional cohorts. Conclusions: CSF biomarkers of angiogenesis are increased in PD, and they are associated with gait difficulties, BBB dysfunction, WMLs, and CMB. Abnormal angiogenesis may be important in PD pathogenesis and contribute to dopa-resistant symptoms.